DEVELOPMENT OF INTERACTIVE WEB-BASED E-MODULE ON THE SOLAR SYSTEM MATERIALS IN SCIENCE SUBJECT - Nugraha, Muhamad Ardian; Hidayat, Sholeh; Suherman, Suherman (JPSD (Jurnal Pendidikan Sekolah Dasar), 2022)
Abstract This research was designed to develop a solar system E-Modul module for 6th grade elementary school students in science subjects. This research uses a 4D model consisting of 4 steps: Define Design, Development, and Dissemination. The subject of this research was 6th grade students of SD Negeri Saruni 1 Pandeglang. The experts conduct validation in the field of materials and media. Product trial is conducted on students. The data from this trial were collected through observation. The data analysis corresponds to the expectations of learning media products assessed through analysis of the average validity. The feasibility of the solar system e-module material in science subjects is 85% with good enough qualifications, and the feasibility of the material in the e-module is 75% with good qualifications. Based on student assessments of e-module learning on solar system material of science subject obtained an average score of 96% with good qualifications. Based on the data, the teaching materials developed have a high level of validity. The overall validity assessment of this research found that this online learning media has a good level of validity, which means that it can be used as students’ teaching material. Keywords: Media Development; e-modul; Solar System